Chlorine-functionalized keto-enamine-based covalent organic frameworks for CO2 separation and capture - Shinde, Digambar B; Ostwal, Mayur; Wang, Xinbo; Hengne, Amol M; Liu, Yang; Guan Sheng; Kuo-Wei, Huang; Lai, Zhiping (CrystEngComm, 2018)
We report highly chemically and thermally stable chlorine-functionalized CAA-COF-1 and CAA-COF-2. The chlorine-functionalized COFs exhibited enhanced CO2 uptake (by ∼28–44%) in comparison with their pristine COF analogues (TpPa-1 and TpBd). Column breakthrough experiments reveal that CAA-COF-1 and CAA-COF-2 display a high CO2/N2 (10/90) gas mixture selectivity of 95 and 54, respectively. Additionally, CAA-COF-1 exhibits a CO2/CH4 (10/90) column breakthrough selectivity of 29.